Effect of manual therapy versus kinesio taping on tension-type headache in Jouf University female students: A randomized controlled trial - Toson, Rokaia A; Alanazi, Kadi; Alruwaili, Malak; Alruwaili, Reem; Almalki, Weaam; Ali, Zeinab A.; Alsirhani, Hadeel; Allam, Nesma M.; Elsayeh, Shaimaa M. A.; Youssef, Sara S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to evaluate the effectiveness of manual therapy versus Kinesio taping (KT) in treating tension-type headaches (TTH) as they are the most common complaint among university students, significantly impacting their academic performance. A randomized controlled study was conducted, including 45 female students. They were 18-25 years, divided into three groups. The first group (Manual therapy) received manual therapy and relaxation training, the second group (KT) received KT every 72 hours and relaxation exercises while the third group (Control) received relaxation exercises, all for three times/week for 8 weeks. The primary outcome was assessed using the Visual Analogue Scale (VAS) for headache intensity. The secondary measure was the HIT-6 to evaluate the impact of TTH. Post-treatment, all three groups showed a significant reduction in VAS scores compared to pre-treatment (p<0.05). HIT-6 scores significantly decreased in the manual therapy and KT groups (p<0.05), whereas the control group showed no significant change (p>0.05). Additionally, the manual therapy group showed a significantly greater reduction in VAS scores compared to the KT group (p<0.05), although no discernible change was observed in HIT-6 scores (p>0.05). Both manual therapy and KT are useful for treating TTH. However, manual treatment alleviates pain intensity more effectively.